POLITICAL BUDGET CYCLES – GOING BEYOND THE AVERAGE - Wielechowski, Michał (Acta Scientiarum Polonorum. Oeconomia, 2019)
We test whether there are country-specific election cycles present in the public expenditure in the European Union. Using panel data on all 28 current EU Member States from 1995 to 2015, we find in general evidence for an election-induced expansion in total government spending and within the categories of public services, safety, housing, recreation, and education. Our contribution is to combine the notion of targeting specific public spending categories and the occurrence of country-specific political budget cycles in the EU. The results indicate that election cycles vary substantially across countries. We observe a significant election effect in about 77% of our estimates. Two thirds of these observed significant effects represent increased spending in pre-election period.